A Survey of Online Resources on the Development of Lifelong Learning among Students of National Open University of Nigeria - Okpala, Angela Ebele (West African Journal of Open and Flexible Learning, 2021)
The research is a survey of online information resources on the development of lifelong learning. In order to achieve this, a questionnaire validated by experts in the field was administered to 150 students randomly selected from the 8 faculties of National Open University of Nigeria (NOUN). Descriptive statistics, using mean and ttest were employed for data analysis. Results revealed that NOUN students accessed online information resources at least once a week (M= 3.33), mostly through their phones (M=3.60) and from cybercafé (M=3.36) or their homes (M=3.34). Further investigation revealed that resources consulted online were for the following purposes and in this order: self-development (M=10.83), research (M=4.33), daily living (M=3.69), study (M=3.67) and relaxation (M=3.59). Types of resources mostly consulted online were course modules (M=3.56), followed by research reports (M=3.51), students' projects (M=3.41) and research articles (M=3.34) in that order. The t-test result revealed that online information resources had influence on NOUN students' daily living. The t-cal value of 3.016 was found to be greater than the t-tab value of 1.650 given 298 degrees of freedom at 0.05 level of significance. It also revealed that online information resources had influence on NOUN students' self-development as the t-cal value of 2.017 was found to be greater than the t-tab value of 1.650 given 298 degrees of freedom at 0.05 level of significance. Some challenges that were found to militate against the use of online information resources were: too many online databases (M=2.95), slow internet speed (M=2.89), slow internet connectivity (M=2.89), inadequate guidance and training (M=2.89) and lack of information literacy skills (M=2.87). It was recommended that students should be encouraged to use online information resources. Libraries should be equipped with online databases and facilities for easy access. Also, the cost of laptops and data bundles should be subsidized by institutions for their students especially for those in open and distance learning institutions. Abstrait La recherche est une enquête sur les ressources d'information en ligne sur le développement de l'apprentissage tout au long de la vie. Pour y parvenir, un questionnaire validé par des experts du domaine a été administré à 150 étudiants sélectionnés au hasard parmi les 8 facultés de la National Open University of Nigeria (NOUN). Des statistiques descriptives, utilisant la moyenne et le test t ont été utilisées pour l'analyse des données. Les résultats ont révélé que les étudiants du NOUN accédaient aux ressources d'information en ligne au moins une fois par semaine (M = 3,33), principalement via leur téléphone (M = 3,60) et depuis un cybercafé (M = 3,36) ou leur domicile (M = 3,34). Une enquête plus approfondie a révélé que les ressources consultées en ligne visaient les objectifs suivants et dans cet ordre : développement personnel (M=10,83), recherche (M=4,33), vie quotidienne (M=3,69), étude (M=3,67) et relaxation ( M=3,59). Les types de ressources les plus consultés en ligne sont les modules de cours (M=3,56), suivis des rapports de recherche (M=3,51), des projets d'étudiants (M=3,41) et des articles de recherche (M=3,34) dans cet ordre. Le résultat du test t a révélé que les ressources d'information en ligne avaient une influence sur la vie quotidienne des étudiants du NOUN. La valeur t-cal de 3,016 cela a été trouvé supérieure à la valeur t-tab de 1,650 étant donné 298 degrés de liberté à un niveau de signification de 0,05. Il a également révélé que les ressources d'information en ligne avaient une influence sur le développement personnel des étudiants du NOUN, car la valeur tcal de 2,017 a été trouvé supérieure à la valeur t-tab de 1,650 étant donné 298 degrés de liberté au niveau de signification de 0,05. Certains défis qui se sont trouvé militer contre l'utilisation des ressources d'information en ligne étaient : trop de bases de données en ligne (M = 2,95), une vitesse Internet lente (M = 2,89), une connectivité Internet lente (M = 2,89), des conseils et une formation inadéquats (M =2,89) et le manque de compétences en littératie informationnelle (M=2,87). Il a été recommandé d'encourager les étudiants à utiliser les ressources d'information en ligne. Les bibliothèques devraient être équipées de bases de iii données en ligne et d'installations pour un accès facile. En outre, le coût des ordinateurs portables et du forfait de données devrait être subventionné par les établissements pour leurs étudiants, en particulier pour ceux des établissements d'enseignement ouvert et à distance.